LITERARY ANALYSIS OF "WAITING FOR GODOT" BY SAMUEL BECKETT AND "FAREWELL, GULSARI" BY CHINGIZ AYTMATOV: A COMPARATIVE STUDY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This paper presents a comparative literary analysis of Waiting for Godot by Samuel Beckett and Farewell, Gulsari by Chingiz Aytmatov, exploring how each work reflects the human condition through distinct philosophical lenses. Beckett’s play, rooted in the Theatre of the Absurd, portrays existential stagnation, uncertainty, and meaninglessness through the endless waiting of Vladimir and Estragon for the elusive Godot. In contrast, Aytmatov’s novella adopts a realist narrative interwoven with symbolism to depict the moral decline, loss of values, and the struggle for purpose experienced by Tanabay and his loyal horse Gulsari within the Soviet socio-political landscape. By comparing themes such as hope and despair, time and memory, human relationships, freedom and oppression, the study highlights how both authors address universal questions of existence despite differing cultural contexts and literary styles. The paper concludes that while Beckett emphasizes the absurdity and futility of human efforts, Aytmatov underscores resilience, emotional attachment, and the tragic consequences of ideological conflict, revealing two parallel yet contrasting portraits of humanity in search of meaning.